Impact Analysis Of Partnership Between Small Retailers And The Sampoerna Retail Community Distribution Company In Sukoharjo Regency - Kurniawan, Aditya Wahyu; Susilo, Agus (UNIVED Press, 2026)
This study aims to analyze the impact of a strategic partnership between small retailers (MSMEs) and the Sampoerna Retail Community (SRC) distribution company in Sukoharjo Regency. This partnership serves as a strategy for empowering MSMEs through coaching, mentoring, and digitalization of store operations. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation of three SRC partner grocery store owners. The results show that the partnership has a positive impact on store modernization, operational efficiency through the